2013
DOI: 10.1119/1.4801354
|View full text |Cite
|
Sign up to set email alerts
|

A Summer Math and Physics Program for High School Students: Student Performance and Lessons Learned in the Second Year

Abstract: F or the past two years, the Eoundations in Physics and Mathematics (FPM) summer program has been held at Indiana University in order to fulfill two goals: provide additional physics and mathematics instruction at the high school level, and provide physics graduate students with experience and autonomy in designing curricula and teaching courses. In this paper we will detail changes made to the program for its second year and the motivation for these changes, as well as implications for future iterations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Students have reported improved mathematics study skills and heightened awareness of education planning and personal learning styles as a result of program participation (Enriquez, ). Other studies have shown improved mathematics or physics knowledge and skills following participation (Dimitriu & O'Connor, ; Enriquez, ; Timme et al., ). Programs may also produce gains in individual student test scores as well as reduce test score variability among participants (Goonatilake & Bachnak, ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Students have reported improved mathematics study skills and heightened awareness of education planning and personal learning styles as a result of program participation (Enriquez, ). Other studies have shown improved mathematics or physics knowledge and skills following participation (Dimitriu & O'Connor, ; Enriquez, ; Timme et al., ). Programs may also produce gains in individual student test scores as well as reduce test score variability among participants (Goonatilake & Bachnak, ).…”
Section: Introductionmentioning
confidence: 92%
“…Other studies have shown improved mathematics or physics knowledge and skills following participation (Dimitriu & O'Connor, 2006;Enriquez, 2010;Timme et al, 2013). Programs may also produce gains in individual student test scores as well as reduce test score variability among participants (Goonatilake & Bachnak, 2012).…”
Section: Knowledge Skills and Preparationmentioning
confidence: 99%
“…A general assumption is that more students will major in STEM if they enroll and do well in science and math-based courses during high school. Studies on precollege research programs are limited and often descriptive ( 24 ), and the existing evidence is mixed: some studies have found positive effects on STEM retention, while others have failed to detect any effects on STEM interest, motivation, or retention ( 25 28 ). Several studies with small sample sizes and vague learning outcomes used surveys to determine the impact of such programs ( 29 31 ), but more empirical studies are needed to quantify the efficacy of STEM research programs on students’ interest, pursuit, and retention in STEM.…”
Section: Introductionmentioning
confidence: 99%
“…The existing evidence is mixed at best. While several studies generally found positive effects on student cognitive and motivational outcomes [7][8][9][10][11][12][13], others failed to detect an effect of OST STEM program participation on desirable student STEM outcomes, such as STEM interest and college major [14][15][16]. The mixed findings of prior studies stemmed in part from research designs that relied on small sample sizes and imprecise outcome measures.…”
Section: Introductionmentioning
confidence: 99%